Os controles internos e contábeis na gestão de tesouraria - Pereira, Marcos Augusto Assi (2010)
The activities of Internal Control and Accounting are part of business management, but there is much difficulty in understanding the applicability of the matter, either through ignorance of the benefits or lack of control culture. These activities require a variety of knowledge management, control and corporate governance in addition to ongoing professional development. The control account is derived from the internal control, which determines the policies and procedures of the organization, not counting the accounting and management reports that will be part of the day to day business and explanatory notes. Thus, this study proposes to answer the following question: How companies are implementing internal controls and accounting to support cash management? The accounting errors and fraud are being treated as part of the business or know not? Because of the doubt given, the general aim of this study is to contribute to the process of implementing controls that favor corporate management, developing strategies that facilitate the relationship between theory and practice primarily on the controller. Data collection took two steps. In the first, was held exploratory study by a research literature and documents. In the second, we performed a field survey by questionnaire sent to professionals responsible for implementing corporate controls on small, medium and large companies in the region of Sao Paulo. Qualitative research and descriptive participant seeks to contribute to the disclosure of the methods and methodologies of management controls in the area of treasury and knowledge about the risk of error and fraud in the organization. The result achieved with the questionnaire, together with the definitions and concepts explored in the research literature and documents, shows that companies are implementing controls and some still have difficulty understanding risk management through internal controls and accounting